Persepsi Mahasiswa Manajemen Dakwah 2020 Terhadap Strategi Dakwah Ustadz Hanan Attaki di Media Youtube Dalam Meningkatkan Pengetahuan Ajaran Islam - Zuleha, Siti; Hasnah Nasution, Nurseri (Social Science and Contemporary Issues Journal, 2024)
This research is entitled "2020 Da'wah Management Students' Perceptions of Ustadz Hanan Attaki's Da'wah Strategy on YouTube Media in Increasing Knowledge of Islamic Teachings". The aim of this research is to find out how much 2020 da'wah management students understand about the da'wah strategy used by Ustadz Hanan Attaki, and also to find out how 2020 da'wah management students perceive Ustadz Hanan Attaki's da'wah strategy via YouTube media in increasing knowledge of Islamic teachings. In this research the author used a qualitative method with a descriptive approach. Data collection techniques in this research are observation, interviews and documentation. The location of this research is the Faculty of Da'wah and Communication at UIN Raden Fatah Palembang. The theory used is from Robbin by explaining that perception has 2 indicators, namely acceptance, the reception process is an indicator of the occurrence of perception in physiological life, namely the function of the senses to capture external stimuli, as well as evaluation, external stimuli that have been captured by the senses, then evaluated by individuals. The results of this research are to increase knowledge of Islamic teachings for the 2020 da'wah management students with the values: aqidah, sharia, and morals, the 2020 da'wah management students after listening to lectures from Ustadz Hanan Attaki made their hearts calm, perhaps because his preaching did not corner anyone. group so that after that we can think about how to improve ourselves to be better. As for suggestions from researchers, hopefully the 2020 missionary management students can always be istiqomah and continue to carry out Allah's commands, and not underestimate the teachings of Islam.